Advanced ceramics for dentistry - Shen, James Zhijian; Kosmac, Tomaz (Butterworth-Heinemann, 2014)
The growth of implant and fixed prosthodontics practices in dentistry has created a rapidly increasing demand for advanced ceramics and ceramic processes. Innovations in ceramics and ceramic processes are vital to ensure reliable and affordable dental-restoration solutions with aesthetically pleasing outcomes. The work aims to engage the bioceramics and engineering communities to meet the challenges of modern dental restoration using advanced ceramics. Incorporating fundamental science, advanced engineering concepts, and clinical outcomes, the work is suitable for bioceramicists, ceramics manufacturers, dental clinicians and biologists. State-of-the-art-coverage encompasses bioresorbable ceramics for bone regeneration and bioactivating surfaces of inert, high-strength ceramics for implantation, keeping research knowledge appropriately updatedDiscusses transition from the baseline stable and physically stiff ceramics research into engineering of highly coherent laminate composites for prosthetic crowns and bridgesShowcases current feasible techniques for producing, in cost-effective and materials-saving ways, long-lasting individualized ceramic components with biocompatibility, complexity and high precision.